The study of public administration in India: A chequered journey (?) - Chakrabarty, Bidyut (2014)
Public Administration, as a discipline, is witnessing drawn of a new era in its study, which now by stepping out of its orthodox/conventional mould seeks to create an independent space in Social Sciences. The overzealous endeavour at making Public Administration an instrumental and goal-driven technical exercise has taken out the dynamism of the discipline as an organic search for administrative solutions for socio-economic problems in the country. The discipline is reduced to efforts at building specific skills which are required to address the identified problems without recognizing their socio-economic and political roots. The discussion that follows revolves around those major issues which remain critical in the framing of syllabus and in class teaching. - Reproduced.
Keywords: Public administration - India; Public administration